ANALISA DAN PERANCANGAN E- LEARNING BERBASIS WEB GUNA PENINGKATAN KUALITAS AKADEMIK DI SMP N 3 MAJENANG. - cahyadi, hagni (Jurnal Teknologi dan Bisnis, 2022)
During this learning process in the junior secondary school SMP N 3 Majenang, still conventional, in other words that the learning process between students and teachers can only be made on condition that the meetings between students and teachers in the classroom. One method of teaching emerging in the present is e-learning. E-learning can assist teachers in their teaching materials to distribute without having to be in class by using the internet, it can maximize instructional time in the classroom is limited. In making use of e-learning PHP is used to create web pages and MySQL as the database data storage. The results obtained from the e-learning can be applied and implemented to help teachers and students in junior secondary school SMP N 3 Majenang in facilitating the learning process .